(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
A field trial was laid out to mitigate the detrimental consequences of waterlogging (WL) on morpho-physiology and productivity of soybeans through potassium (K) application. Soybean genotypes AGS383 and G00166 were tested against 4 days of WL at the flowering stage. The K fertilizer was applied as (i) basal (full dose) and (ii) basal (50%) + top dress (50%) after the termination of a flood. The experiment’s results showed that the WL negatively affected leaf greenness, water and chlorophyll (Chl) content, plant height, nodule and pod production, and soybean seed yield. However, the split application of K fertilizer minimized the detrimental effect of WL in the case of AGS383. This genotype produced taller plants, contained more Chl and water, higher nodules, bold seeds, and accumulated higher amounts of mineral nutrients in their grains under WL condition with K as basal + top dress after the termination of a flood. J. Bangladesh Acad. Sci. 47(2); 155-167: December 2023